2006
DOI: 10.1038/nsmb1096
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the exocyst subunit Sec6p defines a conserved architecture with diverse roles

Abstract: The exocyst is a conserved protein complex essential for trafficking secretory vesicles to the plasma membrane. The structure of the C-terminal domain of the exocyst subunit Sec6p reveals multiple helical bundles, which are structurally and topologically similar to Exo70p and the C-terminal domains of Exo84p and Sec15, despite <10% sequence identity. The helical bundles appear to be evolutionarily related molecular scaffolds that have diverged to create functionally distinct exocyst proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 14 publications
4
120
0
1
Order By: Relevance
“…4A). The striking resemblance between Cog4-(525-785) and the known exocyst and Dsl1p structures, particularly those of Sec6p (residues 411-805) (18) and Tip20p (20), provides strong confirmation that at least some of the subunits composing these complexes are descended from a common progenitor. We therefore adopt the domain nomenclature initially proposed by Dong et al (15) and later In the left-hand pair of images, the surface is color-coded by sequence conservation (darker blue is more conserved).…”
Section: Structural Homology Between Cog4 and Other Tethering Complexmentioning
confidence: 77%
See 1 more Smart Citation
“…4A). The striking resemblance between Cog4-(525-785) and the known exocyst and Dsl1p structures, particularly those of Sec6p (residues 411-805) (18) and Tip20p (20), provides strong confirmation that at least some of the subunits composing these complexes are descended from a common progenitor. We therefore adopt the domain nomenclature initially proposed by Dong et al (15) and later In the left-hand pair of images, the surface is color-coded by sequence conservation (darker blue is more conserved).…”
Section: Structural Homology Between Cog4 and Other Tethering Complexmentioning
confidence: 77%
“…Subunits of the COG, exocyst, Dsl1p, and Golgiassociated retrograde protein (GARP) complexes share limited sequence homology (7,13) that has been suggested to reflect convergent evolution (13). Structures, most of them partial, have been reported for one COG complex subunit, two Dsl1p complex subunits, and four exocyst subunits (14)(15)(16)(17)(18)(19)(20); these structures contain one (Cog2p), two (Dsl1p, Sec15, Exo84p), three (Sec6p), four (Exo70p), or five (Tip20p) helix bundle domains. In each of the exocyst and Dsl1p complex structures, the tandem helical domains form an extended, rod-like array (20,21).…”
mentioning
confidence: 99%
“…The X-ray structure revealed that Cog5 adopts a classic α-helical CATCHR fold previously observed in other COG subunits (Cog2, Cog4) and in the Dsl1 (Dsl1, Tip20), exocyst (Sec6, Sec15, Exo70, and Exo84), and GARP (Vps53, Vps54) complexes (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Munc13, a protein implicated in synaptic vesicle docking and fusion, also displays the CATCHR fold (40).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the Protein Data Bank (PDB) using the Dali server (29) revealed strong structural homology with domains A and B of the exocyst subunit Exo70 (Z = 10.2) and somewhat weaker but significant structural homology with other CATCHR-family MTC subunits, including the exocyst subunits Exo84 and Sec6, the GARP complex subunit Vps54, the Dsl1 complex subunits Tip20 and Dsl1, and Cog4 (Z scores ranged from 4.4 to 7.6). Thus, Cog5 joins the growing list of MTC subunits that display the CATCHR fold and are apparentlydespite very low levels of sequence homology-derived from a single evolutionary progenitor (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation